Prediction of Antibiotic Resistance Genes in Cyanobacterial Strains by Whole Genome Sequencing - Duarte Balata; Tânia Rosado; Francisco Pina-Martins; Vera Manageiro; Carina Menezes; Eugénia Ferreira; Octávio S. Paulo; Manuela Caniça; Elsa Dias (Microorganisms)
Cyanobacteria are ubiquitous in freshwater environments, but their role in aquatic resistome remains unclear. In this work, we performed whole genome sequencing on 43 cyanobacterial strains isolated from Portuguese fresh/wastewaters. From 43 available non-axenic unicyanoabacterial cultures (containing only one cyanobacterial strain and their co-occurring bacteria), it was possible to recover 41 cyanobacterial genomes from the genomic assemblies using a genome binning software, 26 of which were classified as high-quality based on completeness, contamination, N50 and contig number thresholds. By using the comprehensive antibiotic resistance database (CARD) on the assembled samples, we detected four antibiotic resistance gene (ARG) variants, conferring resistance in pathogenic bacteria to tetracyclines, fluoroquinolones (adeF-type) and macrolides (ermF-type, mefC-type and mphG-type). Among these, adeF-type was the most prevalent gene, found across 11 cyanobacterial genomes from the Nostocales order. Planktothrix presented the highest variety of close ARG matches, with hits for the macrolide resistance genes ermF-type, mefC-type and mphG-type. An analysis of the genomic assemblies also revealed an additional 12 ARGs in bacteria from the phyla Firmicutes, Proteobacteria and Bacteroidetes, present in the cyanobacterial cultures, foreseeing the horizontal gene transfer of ARGs with cyanobacteria. Additionally, more than 200 partial ARGs were detected on each recovered cyanobacterial genome, allowing for future studies of antibiotic resistance genotype/phenotype in cyanobacteria. These findings highlight the importance of further efforts to understand the role of cyanobacteria on the aquatic resistome from a One Health perspective.